Sub-terahertz memristor switches using MoS2 by liquid–liquid interface assembly - Mingates, T.; Ghatas, M. E.; Deuermeier, J.; Kelly, A. G.; Neilson, J.; Coleman, J. N.; Mendes, L.; Vaz, J. C.; Matos, S.; Lucci, L.; Clemente, A.; Sofer, Z.; et al. (Advanced Science)
This study demonstrates the first application-ready radio-frequency (RF) switches based on memristors fabricated via electrochemical exfoliation and liquid–liquid interfacial assembly. This 2D layer deposition method produces uniform, low-defect bilayer molybdenum disulfide (MoS2) nanosheet networks without the high temperatures or hazardous gases typical of chemical vapor deposition, providing a low-cost, environmentally friendly route toward CMOS-compatible integration. The resulting devices exhibit robust unipolar resistive switching, simplifying biasing and lowering power consumption compared to bipolar solutions. Devices show reproducibility with 104 s retention and 100-cycle endurance. RF characterization confirms reliable operation across 10–110 GHz with low insertion loss (0.42–0.9 dB), isolation above 18 dB, and an intrinsic cut-off frequency of ∼5.4 THz. The viability for integration into energy-efficient wireless communication platforms is assessed by simulation of a 24 × 24 elements reconfigurable intelligent surface. High gain (>21.6 dBi) and efficient beam steering (−60°–60°) across the 26.8–29.1 GHz band demonstrate the utility of these novel non-volatile RF switches in next-generation mmWave communication, including 5G/6G and satellite systems.